If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9n + -15 = 7n + 11 Reorder the terms: -15 + 9n = 7n + 11 Reorder the terms: -15 + 9n = 11 + 7n Solving -15 + 9n = 11 + 7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7n' to each side of the equation. -15 + 9n + -7n = 11 + 7n + -7n Combine like terms: 9n + -7n = 2n -15 + 2n = 11 + 7n + -7n Combine like terms: 7n + -7n = 0 -15 + 2n = 11 + 0 -15 + 2n = 11 Add '15' to each side of the equation. -15 + 15 + 2n = 11 + 15 Combine like terms: -15 + 15 = 0 0 + 2n = 11 + 15 2n = 11 + 15 Combine like terms: 11 + 15 = 26 2n = 26 Divide each side by '2'. n = 13 Simplifying n = 13
| h(x)=x+4 | | 3/5x^2-4/10x=1/5 | | -(8y+2)-(-7y-6)=-2 | | 6x^3-486x=0 | | (h-g)(-4)= | | 0=27x^2-12 | | 1/4(x-8)=3/5 | | -3(2s-2)-6=-3(8s+3)-3 | | 18x-5=3(6-2) | | f(2)=75*a^2 | | a^2-a-203a^2=13a-1/a | | f(2)=75*a^3 | | (f+g)(6)= | | y-3=-3(x+4) | | 2-lnx=ln(x+4) | | 7/9(1-7/9) | | 2x-4+2(2x)+17=-2-5x(16-5) | | 2x+(x^2)=2.1 | | 2-ln(x)=ln(x+4) | | -3/4(32X-5x^2-29) | | c(n-5)= | | 4a^3+2a^2-20a=0 | | s=3v+3k | | x^4+6x^3-4x^2-24x=0 | | 4a^3+2a^2-23a=0 | | ln(x-1)+ln(2)=ln(x+3) | | Y=6.50x+1500 | | 2x^4+8x^3-2x^2-8x=0 | | (18+17)(12+9)-(7*16)(4+2)= | | -12.5=v/5 | | 5/6w=(-3/4) | | 3(x^2)-12x=0 |